1991
DOI: 10.1111/j.1439-0418.1991.tb01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Parasites and predators of the meal moth Plodia interpunctella Hbn. as affected by Bacillus thuringiensis Berl.

Abstract: The interaction between Plodia interpunctella Hbn., parasites and predators and Bacillus thuringiensis Berl. has been investigated. Experiments with the parasite Bracon brevicornis Wesm. previously fed during the larval instar on treated host larvae of P. interpunctella, showed significant reduction in the egg production. The egg incubation and larval duration of the parasite were not affected except at the highest concentration (500 μg). Percentage of formed cocoons was significantly reduced at all tested con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 9 publications
3
12
0
Order By: Relevance
“…Chilcutt and Tabashnik (1997) and Liu et al (2005b) reported similar results. In contrast, Salama et al (1991) reported that growth and reproduction of the braconid parasitoid Bracon brevicornis were adversely affected after feeding honey solutions fortified with Btk HD-1. If Bt kills the host too quickly or retards the growth very severely, the parasitoid does not have sufficient resources to develop.…”
Section: Discussionmentioning
confidence: 84%
“…Chilcutt and Tabashnik (1997) and Liu et al (2005b) reported similar results. In contrast, Salama et al (1991) reported that growth and reproduction of the braconid parasitoid Bracon brevicornis were adversely affected after feeding honey solutions fortified with Btk HD-1. If Bt kills the host too quickly or retards the growth very severely, the parasitoid does not have sufficient resources to develop.…”
Section: Discussionmentioning
confidence: 84%
“…Babrikova et al (1982) and Babrikova and Kuzmanova (1984) reported higher mortality of the lacewing Chrysoperla carnea (Neuroptera: Chrysopidae) when adults, but not when larvae were fed with food contaminated with three different Btspray formulations under laboratory conditions. Petrova and Khrameeva (1989) reported highly deleterious effects of a spray formulation on the predatory mite Phytoseiulus persimilis (Acari: Phytoseiidae), and detrimental effects on Bracon brevicornis (Hymenoptera: Braconidae) were described by Temerak (1980) and Salama et al (1991). However, the field use of Bt-based insecticides following good agricultural practices is generally considered safe (Flexner et al , 1986;Krieg, 1986;Melin & Cozzi, 1989;Croft, 1990, Meadows, 1993Glare & O'Callaghan, 2000).…”
Section: Introductionmentioning
confidence: 93%
“…and Xylocoris flavipes (St,-LAMA et al, 1982;ZAKI,1983, 1984;SALAMA et al, 1991). Thus, the nymphal duration of the predator was significantly increased after feeding on eggs or neonate larvae of the host treated with the pathogen and the consumption of the nymphs was significantly decreased.…”
Section: Effect Of B-exotoxin (Thuringiensin) On O Albidepennismentioning
confidence: 99%